ANALISIS PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN CSR SEBAGAI VARIABEL INTERVENING - Riniyati, Frumensia; Purwanto, Nanang; Sari, Ati Retna (Jurnal Riset Mahasiswa Akuntansi, 2019)
The purpose of this study is to find out the analysis of profitability to firm value, Leverage analysis of company value, profitability analysis to CSR, Leverage analysis of CSR, CSR analysis of company value and indirect analysis of profitability to company value through CSR, and indirect analysis Leverage on Company Value through CSR. This research was conducted at state-owned companies listed on the Indonesia Stock Exchange in the period 2015-2017. The sample used in this study were 23 sample companies. This study uses a path analysis technique (Path Analysis). The results of this study indicate that the first hypothesis of profitability affects the Corporate Social Responsibility (CSR). The second hypothesis shows leverage influences CSR. The third hypothesis shows profitability has an effect on firm value. The fourth hypothesis shows that leverage has an effect on firm value. The fifth hypothesis shows that Corporate Social Responsibility (CSR) affects the value of the company. The sixth hypothesis shows that profitability affects the value of the company through Corporate Social Responsibility (CSR). The seventh hypothesis shows that leverage affects the value of the company through Corporate Social Responsibility (CSR).